2019
DOI: 10.1177/1471301219871168
|View full text |Cite
|
Sign up to set email alerts
|

Collecting self-report research data with people with dementia within care home clinical trials: Benefits, challenges and best practice

Abstract: One-third of people with dementia live in care home settings and in order to deliver better evidence-based care, robust research including clinical trials is required. Concerns have been raised by researchers about the capacity of care home residents with dementia to participate in clinical trials. This includes self-report measures, completion of which researchers have suggested may be unreliable or impossible and may cause distress for residents. Many trials, therefore, utilise only proxy completed outcome m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 24 publications
(32 reference statements)
1
23
0
Order By: Relevance
“…Finally, higher response variability in internal interviewers may suggest that they deviate more often from the predefined standardised interview script [ 46 ]. This is plausible insofar as interviews represent a communication opportunity for older persons [ 9 ]. The risk of digressing into the usual everyday communication is higher in the case of familiar nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, higher response variability in internal interviewers may suggest that they deviate more often from the predefined standardised interview script [ 46 ]. This is plausible insofar as interviews represent a communication opportunity for older persons [ 9 ]. The risk of digressing into the usual everyday communication is higher in the case of familiar nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Snow et al [ 73 ] found that an existing diagnosis of dementia per se does not lead to inaccurate self-reports of depression. Perfect et al [ 74 ] investiged challenges and benefts of using self-reports in research with PWD. They conclude that self-reports can and should be applied in studies with people in all stages of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Given the challenges care homes face, it is perhaps unsurprising that research levels are lower in care homes to other sectors; however, it is also recognised that people in care homes should have the opportunity to participate in research, with initiatives to create a network of 'research-ready care homes' (Goodman and Davies, 2012;Davies et al, 2014;National Institute for Health Research, 2021). Research has reported how research participation can improve wellbeing, through opportunities to socialise with researchers and peers (Perfect et al, 2021); as well as offering a therapeutic activity in being listened to in a meaningful way (Lakeman et al, 2012); access to information and resources, and pride in participation (Castillo et al, 2012). Shepherd et al (2015) discuss, regulatory changes are needed to allow for more inclusive research to be conducted in a timely manner.…”
Section: Care Home Environmentmentioning
confidence: 99%